ANALISIS PREFERENSI, POLA KONSUMSI, DAN PERMINTAAN BERAS TINGKAT RUMAH TANGGA DI KOTA BANDAR LAMPUNG - Pane, Paula Shintia Marbela; Prasmatiwi, Fembriarti Erry; Situmorang, Suriaty (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
As many as 98% of Indonesians eat rice so that the demand for rice is very high and causes various preferences and patterns of rice consumption of consumers. This study uses a survey method by conducting direct interviews with 70 households in Bandar Lampung City. Data analysis tool uses conjoint, descriptive quantitative analysis, and multiple linear regressions. The results showed that most of the households consisted of 4-5 people, with an average income of IDR 3,971,429 per month. Household priorities on rice attributes respectively are rice texture, rice price, rice color, and rice aroma. Bandar Lampung City households like rice that is fluffy cooked rice, the price of rice ranges from IDR 9,000 to IDR 9,500, the color of white rice is clean, and the rice does not produce flavorful rice. Most of the households buy random types of rice in traditional markets with a purchase frequency of 1-4 times a month with a size of 10 kg per pack with an average purchase of 23.91 kg/month. Seventy percent of households eat rice 3 times a day and 30% eat rice 2 times a day. Households that only eat rice 2 times/day usually replace rice with substitute foods such as instant noodles, bread, market snacks, and others. The factors affecting household rice demand are instant noodles, fish prices, and the number of household members. Instant noodles are a substitute for rice, while fish, eggs, and Tempeh are complementary food of rice. Key words: preference, consumption pattern, rice demand